Mitochondrial Respiratory Chain Dysfunction—A Hallmark Pathology of Idiopathic Parkinson’s Disease? - Flønes, Irene H.; Tzoulis, Charalampos (Frontiers in Cell and Developmental Biology, 2022)
Parkinson’s disease (PD) is the most common age-dependent neurodegenerative synucleinopathy. Loss of dopaminergic neurons of the substantia nigra pars compacta, together with region- and cell-specific aggregations of α-synuclein are considered main pathological hallmarks of PD, but its etiopathogenesis remains largely unknown. Mitochondrial dysfunction, in particular quantitative and/or functional deficiencies of the mitochondrial respiratory chain (MRC), has been associated with the disease. However, after decades of research in this field, the pervasiveness and anatomical extent of MRC dysfunction in PD remain largely unknown. Moreover, it is not known whether the observed MRC defects are pathogenic, compensatory responses, or secondary epiphenomena. In this perspective, we give an overview of current evidence for MRC dysfunction in PD, highlight pertinent knowledge gaps, and propose potential strategies for future research.